Drawing chair conformations in learning pharmaceutical chemistry/ Ibtisam Abdul Wahab - Abdul Wahab, Ibtisam (UiTM Perak Press, 2022)
A series of six-hour lectures in introducing organic chemistry to pharmacy learners were designed with practical hours on how to draw chair conformations to represent a three-dimensional representation of closed carbon atoms ring or cyclic structures. The lesson was provided during both face-to-face sessions, and virtual classes when the pandemic semester begun. The students were taught to draw the two-dimensional views of the molecule during their foundation study, prior to the pharmacy undergraduate program. However, when it comes to three-dimensional illustrations, the students should be able to imagine the upper and lower part of a cyclohexane plane, as they would sit on a chair. Such imaginations are important since the carbon atoms are not positionally equivalent. For the purpose of teaching and learning, two students' batches were invited to submit their drawings. Majority of them showed their efforts, as part of the lecture participation. It was found that most corrections would involve the imaginary parallel axis, to draw both equatorial and axial bonding of the cyclohexane, a six-membered hydrocarbon structure. In summary, this drawing exercise could serve the knowledge of the molecular conformations, as they would later observe in chemical structures having higher atomic weight, such as the pharmaceutically important steroidal molecules, with fused five- and six-membered rings.